Redeeming Jocasta: Tawfiq al-Hakim's 'Eastern', 'Arab' reception of Sophocles' Oedipus Tyrannus. (24th December 2018) - Carducci, Karen L
Abstract: Tawfīq al-Ḥakīm's seminal reception of Sophocles' OT offers a useful window into Arabic reception of Greek tragedy, and into later classical receptions more generally. al-Ḥakīm argues that the success of his 'Oedipus the King' rests upon his identity as an 'Arab scholar, an Easterner', who can understand 'the Greek spirit of tragedy' because he 'still retain[s] some part of [his] original religious sense'. Because the pivotal role of his Jocasta has been overlooked, however, some have doubted his achievement in mediating between Greek tragedy and his religious context. Comparing al-Ḥakīm's characterizations of Jocasta with those of his intertexts shows that al-Ḥakīm foregrounds and recasts his Jocasta as a loving, pious mother who follows norms for female behaviour shared by many Muslims and others in the literary scene of 1940s Egypt. By a more pious Jocasta as a foil to Oedipus, al-Ḥakīm does successfully adapt OT to his cultural circumstances. This study underscores the importance of revisiting the religious milieu of the 'receiver' when judging classical receptions.